PLASMA LEAKAGE PROFILES OF DENGUE HEMORRHAGIC FEVER PATIENTS IN RSUD Dr. SOETOMO, SURABAYA, EAST JAVA, INDONESIA JANUARY – JUNE 2014 - Rizaliansyah, Ferdian; Aryati, Aryati; Rusli, Musofa (Indonesian Journal of Tropical and Infectious Disease, 2017)
Plasma leakage is one crucial point of dengue hemorrhagic fever (DHF) that differentiates it from dengue fever (DF). DHF has to meet 4 criteria which are 2 – 7 days of acute fever, hemorrhagic manifestation, thrombocytopenia (â‰¤100.000 cells/mm3) and evidence of plasma leakage. Plasma leakage consists of increasing hematocrit â‰¥20%, hypoalbuminemia or evidence of pleural effusion or ascites. Often doctors only base their DHF diagnosis on the presence of thrombocytopenia. This study analyzed the presence of plasma leakage between adult and pediatric patients with a DHF diagnosis in RSUD Dr. Soetomo in order to make the diagnosis and healthcare services better in the future. This was a retrospective study which used medical records of DHF patients admitted from January to June 2014. 78 cases were included, 24 adult patients (31%) and 54 pediatric patients (69%). 29/78 (37%) patients had no evidence of plasma leakage. No adult patients had ascites whereas 11/54 (20%) pediatric patients presented with ascites. No adult patients had pleural effusion whereas 25/54 (53%) pediatric patients did. Most adult patients that had serum albumin checked had normal albumin levels (12/14 [86%]) while only 14/28 (52%) pediatric patients had normal albumin level. 5/22 (23%) adult patients versus 32/53 (60%) pediatric patients showed hematocrit increments â‰¥20%. Patients admitted with dengue virus infection may currently be often misclassified as DHF because there are no plasma leakage manifestation in some patients.. There are significant differences in plasma leakage manifestations between adult and pediatric patients which poses a theory that pediatric patients are more susceptible to have plasma leakage manifestations than adult patients.